Atherogenic Index of Plasma as a Cardiovascular Risk Marker in Subclinical Hypothyroidism. A Comparative Study with Conventional Lipid Indices - Premjeet Kaur; Gurkirat Gill (Annals of Pathology and Laboratory Medicine, 2026)
Background: Dyslipidemia, characterized by an imbalance in lipid profiles, is a recognized factor in the development of atherosclerosis and cardiovascular diseases. Current evidence suggests that non-traditional serum lipid ratios are more effective than traditional serum lipid parameters in predicting vascular diseases. Therefore, this study aims to investigate the relationship between atherogenic index of plasma (AIP; logarithm TG/HDL-c), Castelli risk index I and II (TG/HDL-c and LDL-c/HDL-c, respectively), and atherogenic coefficient (AC; non-HDL-c/HDL-c) using traditional serum lipid parameters (triglyceride (TG), total cholesterol (TC), LDL cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c)) with TSH in subclinical hypothyroidism. Material and Methods: The study was designed as a hospital-based cross-sectional observational study conducted for a period of four months from January–April 2026, in Central Clinical Laboratory and Department of Medicine of Adesh Institute of Medical Sciences and Research, Bathinda, a tertiary care teaching hospital in Punjab. A total of 200 subjects (100 cases and 100 controls) were enrolled in the study.Results: Lipid parameters including total cholesterol (p=0.001), triglycerides (p=0.001), HDL (p=0.049), LDL (p=0.001), and VLDL (p=0.001) were significantly higher in cases. Atherogenic indices such as AIP, Castelli Risk Index I, Castelli Risk Index II and AC were also significantly elevated (p